Risk averse choices of managed beach widths under environmental uncertainty. (26th July 2021) - Jin, Di; Hoagland, Porter; Ashton, Andrew D.
Abstract: Applying a theoretical geo‐economic approach, we examined key factors affecting decisions about the choice of beach width when eroded coastal beaches are being nourished (i.e., when fill is placed to widen a beach). Within this geo‐economic framework, optimal beach width is positively related to its values for hazard protection and recreation and negatively related to nourishment costs and the discount rate. Using a dynamic modeling framework, we investigated the time paths of beach width and nourishment that maximized net present value under an accelerating sea level. We then analyzed how environmental uncertainty about expected future beach width, arising from natural shoreline dynamics, intermittent large storms, or sea‐level rise, leads to economic choices favoring narrower beaches. Risk aversion can affect a coastal property owner's choice of beach width in contradictory ways: the expected benefits of hazard protection must be balanced against the expected costs of repeated nourishment actions. Recommendations for Resource Managers Because of environmental uncertainty, coastal protection projects are risky investments. It is important to consider the effects of uncertainty on cost–benefit assessments of these projects. Without uncertainty, optimal beach width is positively related to its values for hazard protection and recreation and negatively related to nourishment costs and the discount rate. Uncertainty about future shoreline positions has a negative impact on the choice of an optimal beach width. Risk aversion can affect a coastal property owner's choice of beach width in contradictory ways: a wider beach to protect their home, and a narrower beach if the effectiveness of nourishment is uncertain.